Estudio de factibilidad para la creación de un minimarket en el Cantón Militar de Infantería de Marina en el Municipio de Corozal Sucre (2021)
In this project a feasibility study for the creation of a minimarket in the military canton of infantry of marina in the municipality of corozal sucre was carried out. With this investigation it was found that, although there are national supermarket chains, there are still spaces for the implementation of new businesses for the sale of mass consumer products